535. Harm reduction strategies and positive behaviors of medical providers in mitigating the effects of COVID-19 among HIV-infected children and HIV-exposed infants. (31st December 2020) - Ebeid, Mariam; Smith, Amy; Inagaki, Kengo; Palmer, April; Santos, Roberto
Abstract: Background: There are limited data on the disease course of COVID-19 among children with HIV and among HIV-exposed infants. It is sensible to maximize the preventive effort against SARS-CoV-2 infections in this group of patients using harm reduction strategies and positive behaviors provided by medical providers. Methods: A quality improvement project was started in the 2 nd week of April in our Children's Hospital Subspecialty Clinic caring for children with HIV and HIV-exposed infants on antiretroviral therapy (ART). All patients are offered Telehealth at baseline and at 4 weeks after interventions making sure they remain adherent to their ART, with enough supply of ART for 4 weeks, and discussed harm reduction strategies (hand washing, use of hand sanitizer & face mask, social distancing, shelter-at-home) via telehealth and video clips. The goal was an increase of hand hygiene performance by 25% at 4 weeks after interventions. The number of hand washing and hand sanitizer use per day was categorized as < 5, 5–10, and >10 per day and was analyzed by Cochran-Armitage test for trend. Adherence to ART was categorized as < 50%, 50–90%, >90–100% per week. Results: There are 19 patients included: 11 with HIV infections (9–20 yo) and 8 HIV-exposed infants (2 weeks-6 months old), where parents received the intervention. At baseline, 32% of the participants washed hands >10 times a day, which increased to 71% after intervention (p value: 0.013). While 21% of participants washed hands < 5 times a day at baseline, all participants washed their hands 5 times or more after the intervention. Sanitizer use of >10 times a day increased from 21% to 43% (p value: 0.026). (Fig. 1 and 2) This was notable increase, as 47% used hand sanitizers < 5 times a day pre-intervention. No one was diagnosed with COVID-19, and all remained asymptomatic at 4-week follow up. All children with HIV remained adherent (>90–100% per week) to their ART. Conclusion: The degree of hand hygiene among children with HIV and HIV-exposed infants was increased 4 weeks after the intervention consisting of harm reduction strategies and positive behaviors by medical providers. All patients remained healthy and adherent to ART 4 weeks after the project began. COVID-19 pandemic is an opportunity for impactful health education that can positively affect the patients' life. Disclosures: All Authors : No reported disclosures